The Underlying Causes of Religious Superstition; A Qur’anic Perspective Focusing on Social Exegeses (Tafsīr-i Nimūni and Fī Ẓilāl al-Qurʾān) - Mahdi Farahani; jafar taban; Seyyed Karim | Seyyed Karim Khoobbin Khoshnazar (پژوهش‌های تفسیر تطبیقی, 2022)
Received: 2021/6/8  |   Correction: 2022/1/9   |   Accepted: 2022/1/9The purpose of this article, which is written under the descriptive-analytical method, is to study more closely the phenomenon of religious superstition, as well as to identify the affecting factors that cause it in some people, albeit from the perspective of the Qur’an. The most important are factors such as personal profiteering, defending one’s favorite religion, weakening various viewpoints of opponents, corruption in religion, as well as religious tyranny. Of course, some superstitions such as bidʿa (heresy), taḥrīf (distortion), qīās (analogy), following mutashābihāt (ambiguous similarities), and intentional or unintentional mistakes of the narrator or listener of Hadith are formed sometimes due to the weakness of people’s religious beliefs. Even extremism in matters such as rationalism, traditionalism, religious toleration, or committing ghuluww (exaggeration) for the benefit of making myths seem among the causes of religious superstitions. Anyhow, identifying the causes of superstition is undoubtedly one of the most fundamental steps towards the pathology of this inauspicious phenomenon. Such a crucial task can put preventive mechanisms in front of present religious communities to increase popular religious insight and not fall into the abyss of superstition and its consequences. It seems only by trusting on God and a sheer obedience to the resuscitative teachings of divine leaders on the one hand and relying on human reason and attempting to raise the level of knowledge on the other, this destructive phenomenon can be overcomed.Farahani, M; Khoobbin Khoshnazar, S.K; Taban, J. (2022) The Underlying Causes of Religious Superstition; A Qur’anic Perspective Focusing on Social Exegeses (Tafsīr-i Nimūni and Fī Ẓilāl al-Qurʾān). Biannual Journal of Comparative Exegetical Researches, 8 (15) 139-166. Doi: 10.22091/PTT.2022.6461.1907.